Realizing the Blue Economy Potential in Albania - World Bank (World Bank, Washington, DC, 2020)
The objective of this study is to fill the knowledge gaps to help advance Albania's vision of the Blue Economy, in the context of the country's aim of joining the EU. The two most important sectors with this regard are fisheries and tourism. Both industries are well established and offer the highest potential return on investment when it comes to the Blue Economy and have socio-economic and cultural significance for the coastal communities. The study further extends to cover the challenges of marine plastic pollution and examine possible solutions. For the purpose of cross-sectoral planning and investment coordination, the Blue Economy Development Framework (BEDF) is introduced as a distinct theme. The analysis concludes with a menu of options to develop the marine based economic activities and ultimately accelerate the country's transition towards the Blue Economy. The study reflects Albania's specific circumstances and the opportunities arising from integrated economic development of maritime sectors, including branding a 'Blue Albania' vision that could serve as a blueprint for future innovations in these sectors. Policy and decision makers from multiple institutions representing the GoA, as well as development partners and organizations such as the European Commission, have been consulted in the course of the study preparation.